Snapshots of Evolving Traditions: Jewish and Christian Manuscript Culture, Textual Fluidity, and New Philology - Ingeborg Lied, Liv; Lundhaug, Hugo (De Gruyter, 2017)
Eschewing the search for the hypothetical original, this volume of essays places manuscripts and manuscript culture center stage and provides new readings of texts from various Christian and Jewish traditions in their manuscript contexts. With emphasis on method, the book takes materiality and manuscript practices into consideration, arguing for the significance of realizing the inherent fluidity of textual transmission in a manuscript culture.